2016
DOI: 10.31729/jnma.2822
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Extended-Spectrum β-lactamase and Integron Genes in Klebsiella pneumonia

Abstract: Introduction: Infections caused by Gram negative bacteria, producing extended-spectrum β-lactamase, including Klebsiella pneumoniae are increasing all over the world with high morbidity and mortality. The aim of the present study was determined antimicrobial profile susceptibility and the prevalence of antibiotic resistance genes by multiplex PCR. Methods: In the present study, we obtained one-hundred isolates of K. pneumoniae from different clinical samples. The antibiotic susceptibility testing was done in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
5
3
0
Order By: Relevance
“…In addition, reduced sensitivity towards cephalosporin and carbapenem antibiotics was observed in this study. High resistant rate towards cephalosporins was also reported in previous studies [ 50 , 52 , 62 , 63 ]. Multiple factors such as extensive use of drugs, production of beta-lactamases, or efflux pumps (which actively pump out these antibiotics) are attributable to the rise in the resistance against carbapenems [ 26 , 64 ].…”
Section: Discussionsupporting
confidence: 80%
“…In addition, reduced sensitivity towards cephalosporin and carbapenem antibiotics was observed in this study. High resistant rate towards cephalosporins was also reported in previous studies [ 50 , 52 , 62 , 63 ]. Multiple factors such as extensive use of drugs, production of beta-lactamases, or efflux pumps (which actively pump out these antibiotics) are attributable to the rise in the resistance against carbapenems [ 26 , 64 ].…”
Section: Discussionsupporting
confidence: 80%
“…Similar to aminoglycosides, a wider range of variation was observed in the non-susceptibility of quinolones ranging from below 1% to greater than 90%. The study from Bulgaria, Italy and Romania was in line with our study, while from countries like Germany, Denmark, Iran, and India, the non-susceptibility rate was lower than our study [18,20,21]. Few studies from Nepal showed that the resistance rate is more than 85%, which is quite much than ours [22,24].…”
Section: Discussionsupporting
confidence: 90%
“…and 86%, respectively [19] while study from Iran and India, its resistance was found as 24% and 37.5%, respectively [20,21]. A slightly higher percentage, 41%, was pictured from Nepal [22] that is nearly equal to our study.…”
Section: Discussionsupporting
confidence: 46%
“…A study in the EU/EEA region showed that its resistance per cent ranges from below 1% to greater than 50 [19]. A comparative study from France and Algeria revealed that its resistance was 28% and 86%, respectively, [20] while in a study from Iran and India, the resistance rate was found to be 24% and 37.5%, respectively [21,22]. A slightly lower percentage, 41%, was observed in Nepal [23] which is nearly equal to our study.…”
Section: Discussionmentioning
confidence: 99%